The effect of drainage cannula tip position on risk of thrombosis during venoarterial extracorporeal membrane oxygenation. (April 2023) - Wickramarachchi, Avishka; Khamooshi, Mehrdad; Burrell, Aidan; Pellegrino, Vincent A.; Kaye, David M.; Gregory, Shaun D.
Highlights: Thrombosis is a severe complication during VA ECMO therapy. Inferiorly positioned single-stage cannulae exhibited highest risk of thrombosis. Positioning cannulae inferiorly may lead to blood stagnation. Varying tip positions impacted flow dynamics, thereby influencing thrombosis risk. Tip position and cannula design should be carefully considered prior to cannulation. Abstract: Background and objectives: Venoarterial extracorporeal membrane oxygenation (VA ECMO) is able to support critically ill patients undergoing refractory cardiopulmonary failure. It relies on drainage cannulae to extract venous blood from the patient, but cannula features and tip position may impact flow dynamics and thrombosis risk. Therefore, this study aimed to investigate the effect of tip position of single-stage (SS) and multi-stage (MS) VA ECMO drainage cannulae on the risk of thrombosis. Methods: Computational fluid dynamics was used to model flow dynamics within patient-specific geometry of the venous vasculature. The tip of the SS and MS cannula was placed in the superior vena cava (SVC), SVC-Right atrium (RA) junction, mid-RA, inferior vena cava (IVC)-RA junction, and IVC. The risk of thrombosis was assessed by measuring several factors. Blood residence time was measured via an Eulerian approach through the use of a scalar source term. Regions of stagnant volume were recognised by identifying regions of low fluid velocity and shear rate. Rate of blood washout was calculated by patching the domain with a scalar value and measuring the rate of fluid displacement. Lastly, wall shear stress values were determined to provide a qualitative understanding of potential blood trauma. Results: Thrombosis risk varied substantially with position changes of the SS cannula, which was less evident with the MS cannula. The SS cannula showed reduced thrombosis risk arising from stagnant regions when placed in the SVC or SVC-RA junction, whereas an MS cannula was predicted to create stagnant regions during all tip positions. When positioned in the IVC-RA junction or IVC, the risk of thrombosis was higher in the SS cannula than in the MS cannula due to both high and low shear flow. Conclusion: Tip position of the drainage cannula impacts cannula flow dynamics and, subsequently, the risk of thrombosis. The use of MS cannulae can reduce high shear-related thrombosis, but SS cannulae can eliminate stagnant regions when advanced into the SVC. Therefore, the choice of cannula design and tip position should be carefully considered during cannulation.